(3JYdjbI Ydi BOGH GdHMK ddSeQbfOjs - (3eLghds
(3ChdgG (B:s
(3GdMeO dhGgH GdYbd hGdUdGI Ydi hGVY Gdfbd agPg QSGdI aj BOGH GdHMK hWQb GdefGXQI jMJGL EdjgG cd eMUd eJYdeG cGf Ch eYdeG dJchf Jdc GdBOGH MGaXI dg aj GdHMK hGdefGXQI ef GdVdGdI hgj Sdhc WQjb dG jhUd Edi GdeWdhH (B...s
(3BNQgG (B:s
... (3hdjcf gPG BNQ GdQSGdI aj BOGH GdefGXQI Hbj TjA dGHCS aj GdJfHjg Ydjg hgh Cf cd Yde ehVhY hZGjI heYQa aehVhY gPG GdYde gh GdefGXQI ceG CTGQ Edjg GdeUfa Hbhdg gPg QSGdI aj BOGH GdHMK hZGjI GdMaX Yf GdVdGd JeJs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdadSaI hGdefWbs